Control over communication networks : modeling, analysis, and design of networked control systems and multi-agent systems over imperfect communication channels /: modeling, analysis, and design of networked control systems and multi-agent systems over imperfect communication channels. (2023) - (Electrical engineer), Zheng, Jianying; (Electrical engineer), Xu, Liang; Hu, Qinglei; Xie, Lihua
No abstract available